Hubungan Pengetahuan Mengemudi Aman dan Masa Kerja dengan Perilaku Mengemudi Aman pada Sopir Bus PO. X Kutoarjo - Muhammad Bagus Panuntun; Tutug Bolet Atmojo; Heni Hastuti (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
There was an increase in traffic accident cases at 5.13% from 2015 (96,233 cases) to 2016 (106,644 cases) (BPS, 2019). Those  traffic accidents could be prevented with the high knowledge of safety driving and period of service of the bus driver. The driver can be more skilled and know the risks of his job so that he is more careful and adopts safe driving behavior. This study aims to determine the relationship between safe driving knowledge and period of service with safety driving behavior. This was an analytic-observational research which utilized the cross sectional research design. Respondents are 93 bus driver of PO.  X Kutoarjo. The sampling technique used is simple random sampling. The instruments used in this research were questionnaires to determine the safety driving knowledge, period of service and safety driving behavior. Then the analysis was carried out using the somers’d test and multiple ordinal regression test. Somers'd test result found that there was a significant relation between knowledge of safety driving and safety driving behavior (p = 0.000; r = 0.683). With the same test, there is a significant relation between period of service and safety driving behavior (p = 0.000; r = 0.606). The result of the multiple ordinal regression test shows that knowledge of safety driving and period of service both have an effect on safety driving behavior, and it is known that knowledge of safety driving has a greater impact than period of service on the safety driving behavior. (p = 0.000; OR = 7.677; p = 0.001; OR = 6.060), it means there is a relation of safety driving knowledge and period of service with safety driving behavior. Knowledge is a precursor factor in a person behavior. Drivers who have good knowledge of safety driving will have a high awareness of the importance of driving safely. The period of service have relation with safety driving behavior, the longer drivers period of service have better safety driving behavior.